Energy Mix Optimization from Energy Security Perspective Based on Stochastic Models - Maman, Yaser Kanani; Maleki, Abbas (International Journal of Energy Economics and Policy, 2022)
As a problem, generally, energy security components do not interfere with the calculation of the optimal energy supply situation. Energy security indices so-called 'passive indices' cannot illustrate comprehensive optimal situation. In this paper, we are looking to find a solution to make a framework of the impact of energy security on energy supply in order to obtain comprehensive analysis of the economic optimal point. Method is based on the competition of energy costs to meet demand during the study period. Threats that have been addressed in the energy security are seen as risky and stochastic parameters in the model. The nature of these parameters is of uncertainty type, therefore, based on the probable scenarios of the stochastic model, the perspective of the energy supply system is drawn up based optimizing the supply of different carrier energy. We apply this method on Iran's import of gasoline as a national threat of energy supply. According to the results, in the period when there are threats of energy imports, energy storage is a low-cost and safe way to compensate for the damage caused by threats. Assuming an annual growth of 5%, capacity can be increased to 8 million barrels during the threat period. The optimal index varies in this period between 0.04 and 0.06.